The Urgency of Forming Legislation Regarding Online Loans in Indonesia: Legal Protection Solutions for the Community - Agustini, Shenti; Silalahi, Udin; Sudirman, Lu; Sihombing, Jonker; Ahmad, Faradina (Jurnal Pembaharuan Hukum, 2025)
Technological developments have an impact on the financial sector. One of the innovations that has occurred in the financial industry is regarding online loans. The regulations that apply in Indonesia relating to online loans are only regulated by financial services authority regulations and Bank Indonesia regulations. Meanwhile, online lending practices give rise to various legal issues that can no longer be resolved solely through these regulations. The research aims to analyze the urgency of establishing legislation regarding online loans. The research method used in this research is normative juridical in answering the problem formulation; a juridical and theoretical basis was used, namely the Legal Protection Theory. The research results show that the formation of a special law regarding online loans is very critical because of the widespread practice of online loans carried out by illegal institutions, which causes the rights and obligations between loan givers and recipients to be unbalanced, such as determining very high loan interest with short repayment periods, as well as personal data leaks and various other cases and other cases. Therefore, it is hoped that the establishment of this unique law can provide external legal protection.